Paradoxical embolism - pulmonary thromboembolism and cerebral ischemia due to patent oval foramen, case report - Tapia Pérez, Rafael (2016)
30 to 40% of cerebrovascular diseases are of unknown or cryptogenic origin; they may be related to patent foramen ovale (PFO) with a prevalence of 12 to 30%. We report the case of a 62 year old woman who underwent surgery for a thyroid tumor. In the postoperative period she presented dyspnea, hypoxemia, impaired consciousness and expression aphasia. Transthoracic echocardiography showed dilatation of right chambers, and transesophageal echocardiography revealed a patent foramen ovale (PFO) with the presence of echoes compatible with clots bordering this defect; the brain scan revealed a stroke in the left hemisphere. The presence of clots and PFO intraoperatively confirmed the development of pulmonary embolism and paradoxical embolism.